Pengaruh Pelatihan Dan Pengembangan, Organizational Citizenship Behavior Dan Kompetensi Terhadap Kinerja Guru SD Se-Kecamatan Cijaku - Dedi Mulyadi; Devi Efriani; Indra Edi; Hadi Subhan (E-Journal Studia Manajemen, 2022)
This study aims to obtain information related to job performance variables. Using a causal study through a survey of elementary school teachers throughout Cijaku District, Lebak Regency, Indonesia, for a population of 70 teachers with a sample of 60 teachers using Slovin sampling technique, data for each variable was collected separately by respondents who filled out the questionnaire. The method used in this study is a quantitative survey method, while the analytical techniques used are correlation and regression analysis. The results prove that there is an effect of training and development on job performance, the effect of OCB on job performance, and competence on job performance. Furthermore, there is a joint influence of training and development, OCB and competence on job performance. These findings indicate that organizations need to consider the variables of training and development, OCB and competence, in planning and developing teacher resources at SD Negeri Se – Cijaku District..